Hitler : study of a revolutionary? - Housden, Martyn, 1962- (London ; New York : Routledge, 2000)
Adolf Hitler is perceived to be the most evil political leader of twentieth century Europe. By presenting a critical selection of primary source material this book examines Hitler's background and involvement in the rise of National Socialism, the government of the Third Reich, leadership of the Second World War in Germany and his psychology, to discuss Hitler's credentials as a revolutionary.
Housden examines: 1. the general characteristics of revolutions and revolutionaries 2. Hitler as Agitator, Dictator, Deceiver and Warlord 3. Hitler's architectural and artistic ambitions 4. Hitler's mind and personality. The book investigates what it was that motivated this national leader to achieve such monstrosities which still cast a shadow over Europe today.
Includes bibliographical references (p. [204]-217) and index.
The Roger Griffin ComFas Collection
Keywords: Hitler, Adolf, 1889-1945.; National socialism; Statesmen -- Germany -- Biography; Germany -- Politics and government -- 1918-1933.; Germany -- Politics and government -- 1933-1945.